Evaluasi Kinerja Trayek AKDP Dari Terminal Baruga Ke Berbagai Jurusan Di Wilayah Provinsi Sulawesi Tenggara - Sumariyani, Sumariyani; Lakawa, Irwan; Magribi, La Ode Muh (Universitas Sulawesi Tenggara, 2020)
This study aims to evaluate the current performance of urban transportation within the province and analyze the need for urban transportation modes within the province. The data analysis technique uses mathematical equations with the help of Microsoft Excel Software. The observation point is at the Baruga Terminal of Kendari City. The results showed that the return trip time of the 8 study routes was only 6 routes that met World Bank standards, namely Torobulu, Andoolo, Lainea, Tinanggea, Palangga and Motaha routes. For vehicle frequency, only 4 routes meet World Bank standards, namely Bambaea, Lainea, Tinanggea and Palangga routes. From the aspect of the loading factor, the highest is on the Torobulu, Lainea and Palangga routes, while the lowest is on the Boepinang route. From the aspect of time difference, none of them meet the World Bank's standard values. From the aspect of cycle time, only 1 route does not meet the standard, namely the Boepinang route. The need for city-in-province transportation modes at the Baruga Terminal has not met the standard because the number of vehicles operating is far less than the number of vehicles set by the Southeast Sulawesi Provincial Transportation Service.